Implementasi Pengelolaan Manajemen Keuangan Syariah di Tadika Tinta Khalifah, Sungai Karangan Penang-Malaysia “Perspektif” H. Dadang Husen Sobana M.Ag - Sholawatin Meisya Anggraini; Rahmayati (Universitas Muhammadiyah Surabaya, 2024)
Financial management activities at Tadika Tinta Khalifah Penang, Malaysia are conducted based on data collection from the prevailing situation. This research focuses on understanding the management practices at Tadika Tinta Khalifah, specifically in budget planning, accounting, and auditing. Qualitative research methods are employed for this study, with the owner of Tadika Tinta Khalifah Penang, Malaysia, and the finance staff serving as the respondents. Interviews are utilized as the primary data collection method. The implementation of financial management is tailored to the needs and various costs, requiring collaboration for smooth operation. The Islamic Caliphate's financial management, engaged in non-profit activities, follows a structured approach encompassing initial planning, directing, implementing, financial management, and ongoing reporting. The overarching goal is to enhance overall quality and performance.